BEDIL AND SUFI THOUGHT: A MYSTICAL PHILOSOPHY OF SELF AND THE DIVINE - Sattorova Shalola Bobir Qizi (Western European Studies, 2025)
Abdul-Qadir Bedil (1642–1720), a prominent Persian-language poet and philosopher from the Indian subcontinent, stands as a unique intellectual figure whose works blend Islamic mysticism, metaphysics, and poetic expression. Deeply influenced by Sufism, Neoplatonism, and classical Islamic philosophy, Bedil’s philosophical system is marked by ontological ambiguity, self-inquiry, and a profound sense of metaphysical unity. This article explores the key tenets of Bedil’s philosophical outlook, highlighting his contributions to Islamic thought and the Indo-Persian intellectual tradition
Keywords: Bedil; Sufism; metaphysics